The Contradictory Role of Technology in Finnish Young People’s Images of Future Schools - Elina Nikula; Tero Järvinen; Anne Laiho (Sage Journals, 2025)
The aim of this study is to analyse the views of young people belonging to Generation Z about the role of technology in future schools in 2030. Without listening to young people’s voices, it has been stated that there is a strong need to increase the use of technology and digitalization in teaching and learning. Based on the essays collected from 89 Finnish young people aged 15–18 years from four different regions, this article presents four qualitatively different future images of technology in future schools. Our results show that the representatives of the same generation are divided into different units with different responses to the rapid technological change and hence one of the key formative experiences of their generation.